Molecular Structure, Vibrational, Spectral Investigation and Quantum Chemical DFT Calculations of Poly(N-isopropyl acrylamide-co-nbutyl methacrylate) - Pihtili, Guzin; Hekim, Seda; Pekdemir, Mustafa Ersin (Polymer Soc Korea, 2022)
A new copolymer poly(N-isopropylacrylamide-co-nbutylmethacrylate) was synthesized by free radical solution polymerization process using 2,2'-Azobis(2-methylpropionitrile) as an initiator in 1,4-dioxane at 70 degrees C. The structure of the copolymer was characterized by Fourier Transform Infrared Spectrometer (FTIR), the proton nuclear magnetic resonance (H-1 NMR), and the ultraviolet-visible spectroscopy (UV-vis) method. Theoretically, density functional theory (DFT) (B3LYP) was utilized to identify the molecular geometry and then examine the vibrational frequencies and electrical characteristics of this molecule, with the 6-31G basis set in the ground state. In dichloromethane solution, UV-vis spectra of the molecule were calculated using the Time-Dependent DFT method. H-1 NMR chemical shifts have been calculated with GIAO approximation, and the calculated results show good agreement with experimental chemical shifts.
Keywords: N-isopropylacrylamide; copolymer; HOMO and LUMO; density functional theory; infrared spectrometer